Iterative method for families of nonexpansive maps - S. J. Aneke (Scientia, 2025)
In this paper, we study an iterative method for approximating a common fixed point of a countably family of nonexpansive mappings in a Banach space. Our result is a generalization of the results of Bauschke [1], Maingé [12] and Chidume and Ali [4]. An asymptotic version of this class of operators is also studied and similar results obtained in a Banach space.